Synergistic Antitumor Effect of Thymoquinone Combined with Resveratrol against Human Lung Cancer Cells Line - Al-kharashi, Nouf Abdulkarim Omar (Journal of medical and pharmaceutical sciences, 2022)
Introduction: Thymoquinone (TQ) and resveratrol are natural anticancer and chemo-preventive agents through mechanism(s) that are not fully understood. This study aimed to test the anticancer potential activity of the combination of TQ and Resveratrol, and their underlying mechanisms in the human lung cancer cell line, A549 cells. Materials and methods: The A549 cells were treated with the different concentrations (25, 50, 75, 100, or 200 μM) of TQ, resveratrol, and their combination for 24h. The antiproliferative activity against A549 cells was assessed using (4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and Trypan blue exclusion assay. Apoptosis markers were assessed by using a real-time reverse transcriptase PCR Assay (rRT-PCR). Results : We found that the proliferation of A549 lung cancer cells was inhibited by TQ, and resveratrol and their combination in a concentration-dependent manner, during a defined period. The combination therapy also could inhibit the growth of A549 cells at 25 μM with a 50% inhibitory concentration (IC50) value of 37 ± 3.18μM. These combinations were significantly (P < 0.001) elevated caspase-3, caspase-8, caspase-9, p53, p21, Fas, FasL, and Bax mRNA levels in treating A549 cells compared to the untreated cells. The anticancer effect of this combination is mediated by the activation of the extrinsic and the intrinsic pathways. Conclusion: all these results give a new promising combination with the enhanced anticancer effect.